Formulation of an optimal mix design of stabilized peat columns with fly ash as a Pozzolan - Wong L.S. (Springer Verlag, 2023)
As a foundation soil, peat poses a grave threat to civil engineering construction due to its softness and large compressibility in nature. Hence, it is crucial to research on its cementation mechanism, so that relevant materials can be quantified to stabilize the soil. In this research work, fly ash (FA) was utilized as a pozzolan to enhance the long-term strength accumulation of stabilized peat columns at experimental scale. The research focus was primarily centered on the design of a suitable mixture of Portland composite cement (PCC), calcium chloride (CaCl2), FA and silica sand that can be applied for the development of stabilized peat columns. A laboratory-based approach was initiated to investigate the pertinent factors that influenced unconfined compressive strength of the stabilized peat. It was found that stabilization of peat can be optimally achieved with a mix design at 10 % partial replacement of PCC with FA. The engineering performance of the stabilized peat was assessed by performing unconfined compression and permeability tests. There were progressive patterns of increase in unconfined compressive strength and decrease in coefficient of hydraulic conductivity for test specimens formulated at the optimal mix design. Chemical and morphological evidences on cementation effect and pore reduction in the peat stabilization are traceable from the respective X-ray diffraction and scanning electron microscopy results. A key discovery is that water continued to play a role as a cement dissolving agent that triggered reactivity with FA to precipitate cementing crystals for the binding of the stabilized peat. 2015, King Fahd University of Petroleum and Minerals.